2000
DOI: 10.1093/ejo/22.6.697
|View full text |Cite
|
Sign up to set email alerts
|

The congenitally missing upper lateral incisor. A retrospective study of orthodontic space closure versus restorative treatment

Abstract: Orthodontic treatment for patients with uni- or bilateral congenitally missing lateral incisors is a challenge to effective treatment planning. The two major alternatives, orthodontic space closure or space opening for prosthetic replacements, can both compromise aesthetics, periodontal health, and function. The aim of this retrospective study was to examine treated patients who had congenitally missing lateral incisors and to compare their opinion of the aesthetic result with the dentists' opinions of occlusa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
193
0
17

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(221 citation statements)
references
References 33 publications
5
193
0
17
Order By: Relevance
“…In our experience and from reports in the literature, the majority of patients for whom upper anterior spaces were closed are satisfied with the result 3 .…”
Section: -Opening or Closing: Advantages And Disadvantagessupporting
confidence: 54%
“…In our experience and from reports in the literature, the majority of patients for whom upper anterior spaces were closed are satisfied with the result 3 .…”
Section: -Opening or Closing: Advantages And Disadvantagessupporting
confidence: 54%
“…The limited literature in this area suggests that a higher proportion of patients who have had OSC are satisfied with the appearance of their teeth (93%) compared with those who have had PR (65%) (Robertsson and Mohlin, 2000). De-Marchi and colleagues (De-Marchi et al, 2014) found that patients who had undergone OSC, judged their own teeth to be significantly more attractive than a control group, who had not had orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the high incidence of unilateral cross bites and class III tendency. Male dimensions were lll larger than female dimensions, the left side being more distant from the midline than the right side [30].…”
Section: Malocclusionmentioning
confidence: 86%